Δ15N in deployed macroalgae as a tool to monitor nutrient input driven by tourism activities in Mediterranean islands. (October 2020) - Signa, Geraldina; Andolina, Cristina; Tomasello, Agostino; Mazzola, Antonio; Vizzini, Salvatrice
Abstract: Mediterranean Sea is among the world's leading tourist destinations; however, the sharp increase in tourists during the high season may affect coastal seawater. The main aim of this study was to evaluate the occurrence and temporal variation of anthropogenic nutrients in coastal seawater in relation to tourist flows in three Mediterranean islands (Cyprus, Sicily and Rhodes), through short-term macroalgae deployments, coupled with δ 15 N analysis and GIS mapping. In all islands, an overall increase in macroalgae δ 15 N occurred over the deployment carried out in August in the tourist sites, suggesting the presence of anthropogenic nutrients. Decreasing δ 15 N values occurred at increasing distance from the coastline in two out of the three islands (Cyprus and Sicily). This study revealed the usefulness of the approach used in the assessment of tourism impact in terms of trophic enrichment and its potential to support competent authorities for the development of sustainable coastal management plans. Graphical abstract: Unlabelled Image Highlights: Deployed Cystoseira was a good bioindicator of anthropogenic nutrient enrichment. Macroalgae Δδ 15 N peaked in August compared to June and October in all tourist sites. Macroalgae 15 N-enrichment decreased from landward to seaward in most tourist sites. Δδ 15 N range was −1.4–+1.4‰ denoting low/moderate inputs of anthropogenic nutrients. GIS maps were a powerful tool to represent tourism impact in coastal water.